Cyclophilin-A is bound through its peptidylprolyl isomerase domain to the cytoplasmic dynein motor protein complex - Galigniana, M.D. (2004)
Although cyclophilin A (CyP-A) is a relatively abundant small immunophilin present in the cytoplasm of all mammalian cells, its general function(s) in the absence of the immunosuppressant drug cyclosporin A is not known. In contrast, the high molecular weight hsp90-binding immunophilins appear to play a role in protein trafficking in that they have been shown to link glucocorticoid receptor-hsp90 and p53-hsp90 complexes to the dynein motor protein for retrograde movement along microtubules. These immunophilins link to cytoplasmic dynein indirectly through the association of the immunophilin peptidylprolyl isomerase (PPIase) domain with dynamitin, a component of the dynein-associated dynactin complex (Galigniana, M. D., Harrell, J. M., O'Hagen, H. M., Ljungman, M., and Pratt, W. B. (2004) J. Biol. Chem. 279, 22483-22489). Here, we show that CyP-A exists in native heterocomplexes containing cytoplasmic dynein that can be formed in cell-free systems. Prolyl isomerase activity is not required for forming the dynein complex, but the PPIase domain fragment of FKBP52 blocks complex formation and CyP-A binds to dynamitin in a PPIase domain-dependent manner. CyP-A heterocomplexes containing tubulin and dynein can be formed in cytosol prepared under microtubule-stabilizing conditions, and CyP-A colocalizes in mouse fibroblasts with microtubules. Colocalization with microtubules is disrupted by overexpression of the PPIase domain fragment. Thus, we conclude that CyP-A associates in vitro and in vivo with the dynein/dynactin motor protein complex and we suggest that CyP-A may perform a general function related to the binding of cargo for retrograde movement along microtubules.